The Role of Institutional Trust and Political Accountability in Pakistan: An Empirical Study - Sadiq, Saiqa (European Centre for Research Training and Development UK, 2018)
A substantial literature have attributed that weak political accountability and failure in governmental performance is basis of declining political trust in Asian countries. Thus Pakistan as an Asian country and emerging democracy also facing both challenges of political accountability and governmental performance. Examining political trust in Pakistan data triangulation is used. It is gathered by interviews (n=20) and from previous literature. However, data is thematically analyzed, that is expedient technique for multiethnic country like Pakistan. Therefore, it is find out that weak political accountability and lower government performance have robust trust eroding effects in Pakistan.Thus the overall results are categorical about people lacking trust over political accountability institutions